Essay, interface and comprehension: a methodological proposal on comprehension as a method, interface as a tool and essay as an exposition strategy - da Costa, Carlos Roberto; Geraldo de Oliveira, José (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
This article seeks reinforce, interweaving ideas of authors like Jose M. Català. Carlos Scolari, Steven Johnson, among others linked to the study of the interface, the importance of the essay as a not hieratic way for new searchs. The Essay, due to its ductile nature and ability to establish relationships between various elements, stands as an equivalent structure of the reality it seeks to investigate.